EJBM 2019
DOI: 10.7176/ejbm/11-2-09
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Media Usage on Organizational Performance in the Jordanian Dead Sea Cosmetic Sector

Abstract: Due to the current debate on the positives and negatives of social media, most of the organizations are in an unclear state regarding the adoption of social media. Therefore, the purpose of this paper is to extend previous research on social media use comprising three variables: social media for marketing, social media for customer's relations and services, and social media for information accessibility and its impact on organizational performance in terms of rapid adaptation, time to market, cost reduction, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 53 publications
1
13
0
5
Order By: Relevance
“…Descriptive analysis was carried out to determine the demographic spread of the respondents. The result in Table 1 indicates that male participants were two hundred and forty-three (243) accounting for 92% of the respondents, while females were twenty-two (22) that is 8% of the respondents. The age distribution shows that a greater percentage of managers of nascent firms in the agro-allied sector are young adults 20-30 years old with one hundred and ninety-eight (198) accounting for (75%) of the total respondents.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Descriptive analysis was carried out to determine the demographic spread of the respondents. The result in Table 1 indicates that male participants were two hundred and forty-three (243) accounting for 92% of the respondents, while females were twenty-two (22) that is 8% of the respondents. The age distribution shows that a greater percentage of managers of nascent firms in the agro-allied sector are young adults 20-30 years old with one hundred and ninety-eight (198) accounting for (75%) of the total respondents.…”
Section: Resultsmentioning
confidence: 99%
“…SM adoption for some businesses has been fast and for others, it has been gradual (Garcia-Morales et al, 2018). However, most businesses, if not all today, depend on SM to drive their communication needs, share information, and gather reliable data that could be as words, pictures, or videos (Dodokh & Al-Maaitah, 2019).…”
Section: Social Media Usage and Nascent Firms' Competitive Advantagementioning
confidence: 99%
See 2 more Smart Citations
“…Examples of popular social media platforms in the industry include Blogger, Twitter, Facebook, LinkedIn, Flickr, YouTube, Ning, and Igloo. Previous research has shown that social media can be used to improve financial performance [39], [40], organizational learning [41], [42], employee performance [43], [44], and innovation [14], [45]. Rodriguez et al [46] claimed that social media positively guided customer orientation activities and ultimately affected sales and business performance.…”
Section: ) Srm and Crm Practicesmentioning
confidence: 99%